Stroke Risk and Treatment in Patients with Atrial Fibrillation and Low CHA2DS2‐VASc Scores: Findings From the ORBIT‐AF I and II Registries. Issue 16 (21st August 2018) - Jackson, Larry R.; Kim, Sunghee; Fonarow, Gregg C.; Freeman, James V.; Gersh, Bernard J.; Go, Alan S.; Hylek, Elaine M.; Kowey, Peter R.; Mahaffey, Kenneth W.; Singer, Daniel; Thomas, Laine; Blanco, Rosalia; et al.
Abstract : Background: Current American College of Cardiology/American Heart Association guidelines suggest that for patients with atrial fibrillation who are at low risk for stroke (CHA2 DS2 VASc=1) (or women with CHA2 DS2 VASc=2) a variety of treatment strategies may be considered. However, in clinical practice, patterns of treatment in these "low‐risk" patients are not well described. The objective of this analysis is to define thromboembolic event rates and to describe treatment patterns in patients with low‐risk CHA2 DS2 VASc scores. Methods and Results: We compared characteristics, treatment strategies, and outcomes among patients with a CHA2 DS2 VASc=0, CHA2 DS2 VASc=1, females with a CHA2 DS2 VASc=2, and CHA2 DS2 VASc ≥2 in ORBIT‐AF (Outcomes Registry for Better Informed Treatment of Atrial Fibrillation) I & II. Compared with CHA2 DS2 VASc ≥2 patients (84.2%), those with a CHA2 DS2 VASc=0 (60.3%), 1 (69.9%), and females with a CHA2 DS2 VASc score=2 (72.4%) were significantly less often treated with oral anticoagulation ( P <0.0001). Stroke rates were low overall and ranged from 0 per 100 patient‐years in those with CHA2 DS2 VASc=0, 0.8 (95% confidence interval [CI] [0.5–1.2]) in those with CHA2 DS2 VASc=1, 0.8 (95% CI [0.4–1.6]) in females with a CHA2 DS2 VASc score=2, and 1.7 (95% CI [1.6–1.9]) in CHA2 DS2 VASc ≥2. All‐cause mortality (per 100 patient‐years) was highest in females with a CHA2 DS2 VASc score=2 (1.4) (95% CI [0.8–2.3]), compared with patients with a CHA2 DS2 VASc=0 (0.2) (95% CI [0.1–1.0]), and CHA2 DS2 VASc=1 (1.0) (95% CI [0.7–1.4]), but lower than patients with a CHA2 DS2 VASc ≥2 (5.7) (95% CI [5.4–6.0]). Conclusion: The majority of CHA2 DS2 VASc=0‐1 patients are treated with oral anticoagulation. In addition, the absolute risks of death and stroke/transient ischemic attack were low among both male and females CHA2 DS2 VASc=0‐1 as well as among females with a CHA2 DS2 VASc score=2. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01701817.